ARK: augmented reality kiosk - Pereira, Pedro (2003)
This paper aims at presenting a very first prototype of an Augmented Reality (AR) system that as been developed in recent months at our research group. The prototype adopts a kiosk format and allows users to directly interact with an AR environment using a conventional data glove. The most relevant feature of this environment is the use of a common monitor to display AR images, instead of employing specific Head-Mounted Displays. By integrating a half-silvered mirror and a black virtual hand, our solution solves the occlusion problem that normally occurs when a user interacts with a virtual environment displayed by a monitor or other projection system.